Kidney Transplantaion - Purwoko, Purwoko; Saputra, Wahyu Yas (This journal is published by the Department of Anesthesiology and Intensive Therapy of Faculty of Medicine, Public Health and Nursing, in collaboration with the Indonesian Society of Anesthesiology and Intensive Therapy , Yogyakarta Special Region Br, 2022)
Chronic Kidney Disease (CKD) is a global public health problem where there is a decrease in kidney function which is marked by a decrease Glomerular Filtration Rate (GFR) slowly over a period of time. The incidence of CKD is increasing rapidly and is expected to become the 5th most common cause of death worldwide by 2040. Kidney transplantation from a living donor is the treatment of choice for most patients with End-Stage Renal Disease (ESRD). However, the absence of specific regulations related to kidney transplantation and guidelines for implementing regulations has become one of the obstacles in the development of kidney transplantation in Indonesia. In addition, a thorough evaluation of potential living donors requires a lot of resources. Early triage of an unsuitable donor will help maximize benefits, minimize risks, and manage expectations for both donors and recipients, and their families. Past and current medical history, family history, and general medical assessment are important to explore the possibility of previously undiagnosed diseases in potential donors. Pre-operative care and preparation as well as types of surgery and anesthesia should also be carried out by a team with adequate expertise, and in an environment where the donor is cared for on a regular basis.